A STUDY ON VARIATIONS OF SALIVARY pH WITH INTAKE OF FOOD - G, Gokul; V, Vishnupriya; R, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Study the changes in salivary pH before and after consumption of food in college students. Methods: The study was conducted on 60 students from Saveetha Dental College by checking the pH of their saliva using a pocket pH meter and the data was entered and compared in SPSS software along with their diet. Results: The data showed significant change in the pH of saliva before and after food intake and consumption on certain food types leads to alkalinity of the oral cavity. Conclusion: This study helped in concluding the role of types of food in changing the pH of the oral cavity and thereby helps the need for proper selection on food is necessary and importance of buffering action in pH maintenance. Keywords: Saliva, pH, food